Republic of Congo : Joint Staff Advisory Note on the Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2012)
This note reviews the Republic of Congo's Poverty Reduction, Growth and Employment Strategy Paper (PRSP). PRSP outlines a comprehensive framework for the reduction of poverty and emphasizes diversifying the economy to generate employment, provide social services and reduce the vulnerability of its citizens, and strengthen good governance. It can be further strengthened by setting clear, realistic targets, prioritizing and sequencing goals and plans to achieve those goals, and creating systems for monitoring and evaluating the specific projects undertaken.